2020
DOI: 10.1021/acsinfecdis.0c00007
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Promotes the Proliferation and Migration of Esophageal Squamous Cell Carcinoma through the miR-194/GRHL3/PTEN/Akt Axis

Abstract: Recent studies have revealed that Porphyromonas gingivalis is closely related to the occurrence and progression of esophageal squamous cell carcinoma (ESCC). However, the underlying mechanism of P. gingivalis in ESCC has not been well elucidated. To explore the mechanism of P. gingivalis infection in ESCC, cellular proliferation, invasion, and migration models of KYSE-30 and KYSE-150 cells infected by P. gingivalis at a multiplicity of infection (MOI) of 10 were established. The results showed that P. gingival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Another critical conclusion was that exosomal miR‐139‐5p could downregulate PTEN and trigger the ERK/MMP‐2 pathway. It was stated that PTEN was strongly connected to various tumors, including breast, endometrial and esophageal squamous cell carcinomas 31–33 . More specifically, PTEN was also found to play a part in trophoblast cell proliferation and PE development regulated by long noncoding RNA T cell leukemia/lymphoma 6 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another critical conclusion was that exosomal miR‐139‐5p could downregulate PTEN and trigger the ERK/MMP‐2 pathway. It was stated that PTEN was strongly connected to various tumors, including breast, endometrial and esophageal squamous cell carcinomas 31–33 . More specifically, PTEN was also found to play a part in trophoblast cell proliferation and PE development regulated by long noncoding RNA T cell leukemia/lymphoma 6 34 .…”
Section: Discussionmentioning
confidence: 99%
“…It was stated that PTEN was strongly connected to various tumors, including breast, endometrial and esophageal squamous cell carcinomas. [31][32][33] More specifically, PTEN was also found to play a part in trophoblast cell proliferation and PE development regulated by long noncoding RNA T cell leukemia/lymphoma 6. 34 Moreover, strengthened PTEN in HTR-8/SVneo cells displayed partial degeneration of the improved cell infiltration prompted by miR-21.…”
Section: Ameliorative Effect Of Exosomes On Pe Ratsmentioning
confidence: 99%
“…Further, Yuan et al highlighted the ability of P. gingivalis to evade immune surveillance, and they determined that the blockade of immune-checkpoint B7-H4 and lysine demethylase 5b in ESCC conferred resistance against P. gingivalis infection and tumor challenge, proposing them as potential therapeutic targets for controlling P. gingivalis infection and its associated neoplasia [ 86 ]. Furthermore, P. gingivalis can enhance ESCC cell proliferation and metastasis by triggering the NF-κB signaling pathway [ 87 ] or via the miR-194/GRHL3/PTEN/Akt axis [ 88 ].…”
Section: Oncologymentioning
confidence: 99%
“…Although P. gingivalis has been proven to invade gingival epithelial cells [ 12 ], studies on its presence in the epithelium of different sites of the digestive tract are scarce. Previously, our group found that P. gingivalis detection may be a high-risk factor for esophageal squamous cell carcinoma (ESCC), and was correlated with the development of esophageal cancer [ 13 17 ]. These reports indicate that chronic bacterial infection with P. gingivalis is an important etiological factor of tumor development and progression.…”
Section: Introductionmentioning
confidence: 99%